2017
DOI: 10.1155/2017/6953156
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Stress Response as a Therapeutic Target for CNS Injuries

Abstract: Central nervous system (CNS) injuries, caused by cerebrovascular pathologies or mechanical contusions (e.g., traumatic brain injury, TBI) comprise a diverse group of disorders that share the activation of the integrated stress response (ISR). This pathway is an innate protective mechanism, with encouraging potential as therapeutic target for CNS injury repair. In this review, we will focus on the progress in understanding the role of the ISR and we will discuss the effects of various small molecules that targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 78 publications
(114 reference statements)
0
16
0
Order By: Relevance
“…Studies have shown that factors released by HIV‐infected immune cells in the brain as well as ARV compounds (Finzi et al, 1997; Saylor et al, 2016) can activate the ISR, suggesting a role in HAND pathogenesis and/or persistence (Akay et al, 2012; Akay et al, 2014; Gannon et al, 2017; Lindl et al, 2007; Stern et al, 2018). ISR activation causes phosphorylation of eIF2α which attenuates global protein translation while promoting translation of certain stress response proteins including ATF4 (Pakos‐Zebrucka et al, 2016; Romero‐Ramírez et al, 2017). Since myelin synthesis requires massive production of lipids and proteins, it is unsurprising that the ISR has been implicated in numerous myelin disorders that share a common white matter pathology also observed in HAND (Clayton & Popko, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that factors released by HIV‐infected immune cells in the brain as well as ARV compounds (Finzi et al, 1997; Saylor et al, 2016) can activate the ISR, suggesting a role in HAND pathogenesis and/or persistence (Akay et al, 2012; Akay et al, 2014; Gannon et al, 2017; Lindl et al, 2007; Stern et al, 2018). ISR activation causes phosphorylation of eIF2α which attenuates global protein translation while promoting translation of certain stress response proteins including ATF4 (Pakos‐Zebrucka et al, 2016; Romero‐Ramírez et al, 2017). Since myelin synthesis requires massive production of lipids and proteins, it is unsurprising that the ISR has been implicated in numerous myelin disorders that share a common white matter pathology also observed in HAND (Clayton & Popko, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The ISR is a cytoprotective mechanism which is activated in response to stressors including viral infections. However, if the stress is unresolved, cell death ensues (Pakos‐Zebrucka et al, 2016; Romero‐Ramírez, Nieto‐Sampedro, & Barreda‐Manso, 2017). We previously reported that ARV compounds from the protease inhibitor class ritonavir, lopinavir, saquinavir and darunavir, inhibited oligodendrocyte maturation, in vitro, while ritonavir also inhibited myelin protein production, in vivo (Festa et al, 2019; Jensen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A cytoprotective ISR is triggered by a variety of stresses such as protein misfolding and aggregation, oxidative stress, and mitochondrial dysfunction and its pharmacological enhancement provides neuroprotection in several models of neurodegeneration [ 29 ]. On the other hand, NMDAR-mediated excitotoxicity is involved as well in several brain diseases [ 20 ] but its link with the ISR is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…to mobilize needed resources, with the intent of returning the body back to a homeostatic level [72]. The stress response is considered relatively conserved across vertebrates [73][74][75][76][77] and includes the limbic system, the central nervous system, the stress or hypothalamic-pituitary-adrenal (HPA) axis, and the thyroid or hypothalamic-pituitary-thyroid axis (HPT), all of which can directly or indirectly influence the HPG axis [77][78][79][80]. Selection should favor an optimized stress response in which an organism's physiological and behavioral responsiveness to perturbation promotes its survival and, ultimately, reproduction.…”
Section: Discussionmentioning
confidence: 99%